Removal of Phenolic Compounds from Aqueous Solution by Using Agricultural Waste (Al-Khriet) - A.K. Al-jandeel, Hayder (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Adsorption techniques are widely used to remove organics pollutants from waste water particularly, when using low cost adsorbent available in Iraq. Al-Khriet powder which was found in legs of Typha Domingensis is used as bio sorbent for removing phenolic compounds from aqueous solution. The influence of adsorbent dosage and contact time on removal percentage and adsorb ate amount of phenol and 4- nitro phenol onto Al-Khriet were studied. The highest adsorption capacity was for 4-nitrophenol 91.5% than for phenol 82% with 50 mg/L concentration, 0.5 gm. dosage of adsorbent and pH 6 under a batch condition. The experimental data were tested using different isotherm models. The results show that Freundlich model resulted in the best fit also the kinetic study make it clear that the adsorption process proceeded according to the pseudo second order model.